Wallimahtul Ursy as the Embryo of the Birth of Marriage Registration According to Islamic Law - Latupono, Barzah (Yuridika, 2024)
This research aims to provide an illustration that by carrying out a marriage according to Islamic religious law without going through a marriage notification at the KUA, known as nikah sirri, then making a walimah to announce the marriage shows that there are no obstacles to the marriage being carried out.This research uses normative juridical research methods using primary, secondary and tertiary legal materials as well as statutory regulations and legal concepts.The results of the research show that if the sirri marriage is carried out by the guardian as a form of announcement to the public, then the marriage is considered valid because the conditions have been fulfilled and are in harmony and can be published which can be interpreted as a form of recording. because previously there was no institution for marriage registration. Walimah shows that a valid marriage has been carried out according to Islamic law, so that there are no longer any obstacles to the marriage. The function of recording according to state law is for everyone to know and serve as evidence for the parties. Making a walimah means wanting to announce the marriage and provide evidence to the public and government that a valid marriage has been carried out so that it can be reported administratively for recording.